Study on tensile mechanical properties of polymer cement composite joint sealant under negative temperature. Issue 1 (February 2021) - Wang, Zhihang; Xu, Jinyu; Meng, Xin; Huang, Zhe; Xia, Wei
Abstract: Tensile tests were carried out on polymer cement composite joint sealant(PCJS) after different negative temperature action time. By testing the tensile strength index, tensile deformation index and tensile energy consumption index of PCJS, the effect of negative temperature action time on the tensile mechanical properties of PCJS was studied. The results show that with the extension of the negative temperature, the tensile strength of PCJS continues to increase, the tensile elongation at break and the tensile toughness first increase and then decrease, the tensile peak strain and the tensile pre-peak toughness keep decreasing. After 1 d of negative temperature, the tensile elongation at break and the tensile toughness of PCJS were the largest.